Study of Building Aerodynamics for Designing Natural Ventilation System - Gupta, Anuj; Vats, Bhavyanidhi; Ahmed, Anwer; Verma, Sushant; Kumar Sharma, Vipul (International Journal of Engineering and Technology, 2018)
Study of building aerodynamics is an important part of building design because aerodynamic factor helps us to design considering wind velocity. If building has not been designed with this factor, wind may damage external walls of the building. In this study, 2D and 3D models of building in three different shapes has been considered for the simulation. Cylindrical, cuboidal and back stair type building has been considered with steady state, laminar air flow and building walls with no slip condition problem. With the study of air flow in the surrounding of the building, effect of air flow on the ventilation system will be concluded in this paper.Â Â